2019
DOI: 10.1016/j.rmcr.2019.100901
|View full text |Cite
|
Sign up to set email alerts
|

Real-time PCR and targeted next-generation sequencing in the detection of low level EGFR mutations: Instructive case analyses

Abstract: Background Allele specific real-time PCR and next-generation sequencing (NGS) are widely used to detect somatic mutation in non-small cell lung cancer (NSCLC). Both methods commonly use formalin-fixed paraffin-embedded (FFPE) tissues as diagnostic materials. Real-time PCR has the advantage of being easy to use and more tolerant of variable DNA quality, but has limited multiplex capability. NGS, in contrast, allows simultaneous analysis of many genomic loci while revealing the exact sequence change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…It was observed that the NGS-based assay showed high sensitivity in testing tumour biomarker genes in plasma cfDNA as gene allele variant fraction of less than 0.1% and the copy number of gene allele variant of less than 1 copy/mL plasma were also successfully detected (figures 1 and 3). This confirms other studies in which the deep sequencing approach showed higher detection sensitivity in testing tumour biomarker gene variants in cfDNA than qPCR and MassArray-based assays 30 32 33…”
Section: Discussionsupporting
confidence: 87%
“…It was observed that the NGS-based assay showed high sensitivity in testing tumour biomarker genes in plasma cfDNA as gene allele variant fraction of less than 0.1% and the copy number of gene allele variant of less than 1 copy/mL plasma were also successfully detected (figures 1 and 3). This confirms other studies in which the deep sequencing approach showed higher detection sensitivity in testing tumour biomarker gene variants in cfDNA than qPCR and MassArray-based assays 30 32 33…”
Section: Discussionsupporting
confidence: 87%
“…Considering this, we speculate that there is no literature concerning other tumors until now because other studies that analyzed this specific AR mutation focused primarily on breast and prostate cancer. Besides, we used a qPCR-based method to detect cfDNA mutations, which is shown to have a better sensitivity to detect low allele fraction variants than sequencing [ 31 ]. Still, the underlying mechanisms of the involvement of AR p.H875Y mutation in the carcinogenesis of these cancer types should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this interesting analysis pointed out the urgent need of further investigations in order to clarify the mechanism of differential responses to TKIs. In the study by Zhang et al [54], patients with a sensitive EGFR alteration such as 19Del/p.L858R/p.L861Q, plus a p.T790M de novo or an exon 20 insertion exhibited the worst clinical outcomes [116], [118]. This could be clarified as they were treated with first-and second-generation EGFR-TKIs.…”
Section: Discussionmentioning
confidence: 98%
“…Notably, the presence of coexisting genetic alteration might likely justify resistance to TKIs treatment [116]. Particularly, different clinical trials assessed that the concurrent presence of mutation provides a worse prognosis in EGFR-positive NSCLC patients treated with first-, second-, and third-generation TKIs.…”
Section: Discussionmentioning
confidence: 99%